Editorial [Special Board Members Issue - Prudhomme, Michelle (Anti-Cancer Agents in Medicinal Chemistry, 2009)
ACA-MC is now in its ninth volume. Besides regular general issues reviewing major advances in various areas of anti-cancer agents, two Hot Topic Issues have been published in 2009 with exciting recent developments in the field of enzymes and other proteins inhibitors. For 2010, a large number of authors have proposed review articles covering the latest developments in medicinal chemistry and rational drug design. Several Hot Topic Issues will also be published, the first one on prostate cancer therapy. In this special 2009 Editorial Board Members, nine members of the ACA-MC Editorial Board present various and recent advances in the continuous efforts to develop efficient anti-cancer therapies. The first paper written by Dr. J. Ho reviews the effects of oxymatrine, an active constituent isolated from roots of Sophora flavescens, on cell division of cancer cells. In the second paper, Dr. I. Kostova describes the antitumor properties of titanium and vanadium complexes. Though the exact mechanism of action for these compounds has not been determined, their interaction with DNA seems to be at least partially responsible for their antitumor effects. Dr. Kostova says,“It is a pleasure to thank and express my appreciation to the editorial staff for the work they have been doing and continue to do for the recognition and prosperity of ANTI-CANCER AGENTS IN MEDICINAL CHEMISTRY!” The third paper from Dr. S. Nagini is devoted to hamster buccal pouch carcinogenesis model as a useful system for the study of synthetic and natural chemopreventive agents. In the fourth review, Drs. M. Tolomeo, F. Dieli, N. Gebbia and D. Simoni reported the in vitro and in vivo results obtained with the novel tyrosine kinase inhibitors developed to overcome imatinib resistance in Bcr-Abl expressing hematological disorders. In the fifth paper, the synthesis, the molecular targets, and the antitumor activities of substituted tetrahydro 1-oxopyrano[4,3- b][1]benzopyrans and nanogels for drug delivery are presented by Drs. E. Perchellet, J.-P. Perchellet, C. Ganta, D. Trover, A. Shi, and D. Hua.